Rethinking the Mini-Map: A Navigational Aid to Support Spatial Learning in Urban Game Environments. Issue 12 (2nd December 2018) - Khan, Numair; Rahman, Anis Ur
ABSTRACT: Players in computer games continue to rely on assistance for navigation in the game environment, even after hours of gameplay. This behavior is in contrast to the real world where spatial knowledge of an unfamiliar environment develops with experience and reliance on navigational assistance declines. The slow development of spatial knowledge in virtual environments can be attributed to the use of turn-by-turn navigational aids. In the context of computer games, the most common form of these aids is a "mini-map." The use of such aids in computer games is necessitated by the demands of immersion and entertainment and, hence, they cannot be entirely discarded. The need, then, is to design navigational aids that support, rather than inhibit, the development of spatial knowledge. The authors propose landmark-based verbal directions as an alternative to mini-maps and report the results of a randomized comparative study conducted to examine the impact of mini-maps and their proposed aid on the development of spatial knowledge in a virtual urban environment. The results confirm the superiority of their verbal aid in terms of spatial knowledge, while mini-maps perform better with respect to navigational efficiency. The authors hope that this study provides a first step toward defining design parameters that govern the tradeoff between navigational efficiency and spatial learning.